Sealing socket with custom healing abutment in case of immediate posterior implant placement: A case report - Ghada Neji; Mohamed Tlili; Raki Selmi; Mootaz Mlouka; Mohamed Salah Khalfi; Faten Ben Amor (SAGE Open Medical Case Reports)
Replacing a hopeless molar with a dental implant is one of the most common treatment modalities in implant dentistry. However, immediate implant post-extraction in the posterior region requires managing the bone gap and ensuring primary closure of the socket. To address this anatomical consideration, several authors have proposed using a custom abutment to seal the socket after immediate implant placement, maintain soft tissue contour, and stabilize the surrounding tissues. For example, the “Sealing Socket Abutment” (SSA) enhances the anatomical emergence profile, which facilitates the biological, prosthetic, and aesthetic integration of the future supra-implant prosthesis. A 32-year-old female patient in good general health consulted the Outpatient and Implantology Department of the dental clinic in Monastir, Tunisia, for the extraction of the root tip of the left first mandibular molar (tooth number 36) and subsequent implant rehabilitation. The patient’s medical history was unremarkable, with no known allergies, or chronic conditions. Follow-up appointments were scheduled to monitor the healing process and ensure successful integration of the implant. The aim of this paper is to present, through this clinical case report, the SSA abutment fabrication protocol using the direct technique and to discuss the advantages and limitations of this technique.